ANALISA KONDISI KERUSAKAN JALAN KABUPATEN TANJUNG API-API – GASING BERDASARKAN METODE SDI - Marpen, Rio (Universitas Muhammadiyah Palembang, 2021)
One of the potential roads in South Sumatra Province is the Tanjung Api-Api - Gasing road. So that good maintenance is needed so that community activities can run smoothly. In this study, the method used to evaluate the level of damage to the Tanjung Api-Api - Gasing road section is the Surface Distress Index (SDI) method. The purpose of this research is to carry out an inventory of current conditions and build a database or geodatabase for the Tanjung Api-api - Gasing district road. Based on the results of the field survey, the entire road width is 4 m and uses rigid pavement. Field survey observations, some field conditions are not good. Where there are still some segments that have a rough arrangement with a detached state. There are some fixes in the form of patches. On roads there is no decline that occurs. The results of the SDI analysis carried out can be concluded that there are 3 segments that are heavily damaged and 1 segment in moderate condition, while the other segments are still in good condition.Key Words : SDI (Surface Distress Index), Rigid Pavement, Tanjung api-api Gasing